2011
DOI: 10.3324/haematol.2011.041277
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse large B-cell lymphoma with involvement of the kidney: outcome and risk of central nervous system relapse

Abstract: BackgroundRenal involvement is uncommon in diffuse large B-cell lymphoma. Recent data suggest that it is an independent risk factor for central nervous system relapse. We reviewed the clinical features, risk of central nervous system involvement, and survival of patients with diffuse large Bcell lymphoma with involvement of the kidney at diagnosis. Design and MethodsAll patients with diffuse large B-cell lymphoma and renal involvement diagnosed from January 1, 1982 to December 31, 2008 at the British Columbia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 36 publications
2
69
0
1
Order By: Relevance
“…In most of the cases it is secondary and occurs by hematogenous spread or by direct extension of the disease from a retroperitoneal mass. Villa et al concluded that there is a high incidence of central nervous system relapse in patients with DLBCL and kidney involvement at diagnosis [18][19][20]. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In most of the cases it is secondary and occurs by hematogenous spread or by direct extension of the disease from a retroperitoneal mass. Villa et al concluded that there is a high incidence of central nervous system relapse in patients with DLBCL and kidney involvement at diagnosis [18][19][20]. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1 It is an uncommon event, with incidence numbers ranging from 2% to 7% in large cohorts dominated by aggressive B-cell lymphomas. [2][3][4][5][6][7][8][9] Risk factors for CNS relapse have not been entirely consistent between studies but have included specific anatomical sites, high proliferation rate, and advanced disease. [2][3][4]8,10 The addition of intrathecal treatment to chemotherapy has commonly been used to avoid CNS relapse in patients deemed at high risk.…”
Section: Introductionmentioning
confidence: 99%
“…5,[19][20][21] A growing body of evidence indicates a higher CNS relapse rate among patients with renal involvement by lymphoma. Villa and colleagues 22 reported CNS involvement in 36% of patients with DLBCL with renal involvement. Similarly, Tai and colleagues 23 found that renal involvement was the primary risk factor for CNS relapse, ahead of even breast or testis involvement.…”
Section: Guidelines For Diagnosis Prevention and Management Of Centrmentioning
confidence: 99%